2001
DOI: 10.1046/j.1467-789x.2001.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and health‐related quality of life

Abstract: Although it is well documented that obesity is strongly associated with morbidity and mortality, less is known about the impact of obesity on functional status and health-related quality of life (HRQL). However, in recent years research has been conducted to estimate the impact of obesity on HRQL, and to determine the effects of weight reduction on HRQL. The majority of published studies indicate that obesity impairs HRQL, and that higher degrees of obesity are associated with greater impairment. Obesity-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
500
2
23

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 622 publications
(574 citation statements)
references
References 61 publications
49
500
2
23
Order By: Relevance
“…The very beginnings of this impact are apparent in the variation in scores seen in the obese children on question 3, which showed a slight decrease in the ability to enjoy activities with friends and family. The negative effect obesity has on health and QOL has been shown repeatedly in adults (Fontaine & Barofsky, 2001). …”
Section: Quality Of Lifementioning
confidence: 94%
See 4 more Smart Citations
“…The very beginnings of this impact are apparent in the variation in scores seen in the obese children on question 3, which showed a slight decrease in the ability to enjoy activities with friends and family. The negative effect obesity has on health and QOL has been shown repeatedly in adults (Fontaine & Barofsky, 2001). …”
Section: Quality Of Lifementioning
confidence: 94%
“…Research has shown poor quality of life in obese children (Fontaine & Barofsky, 2001;Schwimmer et al, 2003). However, this area of research needs to be expanded to include comorbidities such as asthma.…”
Section: Significance To Nursingmentioning
confidence: 99%
See 3 more Smart Citations